Cardioprotective effects of Baccharis trimera (Less.) DC in a rodent model of hookah, alcohol, and energy drink exposure - Amaral, Eduarda Carolina; da Silva, Gustavo Ratti; Braga, Fernanda de Abreu; Palozi, Rhanany Alan Calloi; Lorençone, Bethânia Rosa; Marques, Aline Aparecida Macedo; Moreno, Karyne Garcia Tafarelo; Leite, Patrícia Regina Terço; Barboza, Lorena Neris; Souza, Roosevelt Isaias Carvalho; dos Santos, Ariany Carvalho; Lovato, Evellyn Claudia Wietzikoski; et al. (My University, 2023)
This study proposes an unpreceded model of cardiovascular disease by combining alcohol and energy drink intake with hookah smoking to investigate the cardiovascular effects of Baccharis trimera (Less.) DC., a medicinal plant used to treat dyslipidemia. For 10 weeks, Wistar rats (n=8) received alcohol (10% ad libitum) and energy drink (2 mL/kg) and/or were exposed to hookah smoke (1 hour/day). In the last 4 weeks, the animals received daily treatment with vehicle (filtered water) or ethanol soluble fraction of B. trimera (30, 100 and 300 mg/kg). Electrocardiography was performed. Systolic, diastolic, and mean blood pressure, heart rate, and plasmatic cholesterol, triglycerides, urea, creatine, aspartate, and alanine aminotransferase levels were determinate. The heart, aorta, and kidneys were histopathological evaluated. In isolation the risk factors altered all the evaluated parameters and when the risk factors were associated, a synergistic effect was observed. Treatment with B. trimera reversed these cardiovascular changes.
Efectos cardioprotectores de Baccharis trimera (Less.) DC en un modelo de roedor de exposición a narguile, alcohol y bebidas energéticas
Keywords: Alcohol; Baccharis trimera; Cardiovascular diseases; Carqueja; Hookah; Tobacco